Systematic review of misdiagnosis of conversion symptoms and "hysteria". - Stone, J; Smyth, R; Carson, A; Lewis, S; Prescott, R; Warlow, C; Sharpe, M (2005)
OBJECTIVE: Paralysis, seizures, and sensory symptoms that are unexplained by organic disease are commonly referred to as "conversion" symptoms. Some patients who receive this diagnosis subsequently turn out to have a disease that explains their initial presentation. We aimed to determine how frequently this misdiagnosis occurs, and whether it has become less common since the widespread availability of brain imaging. DESIGN: Systematic review. DATA SOURCES: Medline, Embase, PsycINFO, Cinahl databases, and searches of reference lists. REVIEW METHODS: We included studies published since 1965 on the diagnostic outcome of adults with motor and sensory symptoms unexplained by disease. We critically appraised these papers, and carried out a multivariate, random effect, meta-analysis of the data. RESULTS: Twenty seven studies including a total of 1466 patients and a median duration of follow-up of five years were eligible for inclusion. Early studies were of poor quality. There was a significant (P < 0.02) decline in the mean rate of misdiagnosis from the 1950s to the present day; 29% (95% confidence interval 23% to 36%) in the 1950s; 17% (12% to 24%) in the 1960s; 4% (2% to 7%) in the 1970s; 4% (2% to 6%) in the 1980s; and 4% (2% to 6%) in the 1990s. This decline was independent of age, sex, and duration of symptom in people included in the studies. CONCLUSIONS: A high rate of misdiagnosis of conversion symptoms was reported in early studies but this rate has been only 4% on average in studies of this diagnosis since 1970. This decline is probably due to improvements in study quality rather than improved diagnostic accuracy arising from the introduction of computed tomography of the brain.